Glomeruloesclerose segmentar e focal pós transplante renal - Siliano, Juliana Mansur [UNIFESP] (2019)
Background: FSGS recurs in 30% of adults and in 80% of pediatric kidney transplant recipients. There is no standard of care treatment. Aim: The purpose of this study was to evaluate clinical and laboratorial characteristics, response to treatment and renal outcomes of patients with post transplant FSGS. Methods: The study includes a retrospective and a prospective analysis of patients with post transplant FSGS. The single-center cohort study 1 analyzed patients treated with plasmapheresis (PP) and combinations of high dose steroids, cyclosporine and rituximab. The prospective single-center study 2 applied multitarget treatment consisting of cyclosporine, prednisone and PP to assess therapeutic response and adverse events. The study 3 evaluated retrospectively data from both previous studies together. Results: Among 61 patients with post transplant FSGS included in study 1 the median time to diagnosis was 19 days. The incidence of first biopsy-confirmed FSGSr was 18% reaching 52.4% with follow-up biopsies. During PP treatment 54% of the patients developed infectious complications. PP was discontinued in 37% of patients due to treatment failure (no remission or graft loss) and in 26% due to AE. All patients who discontinued PP due to AE did not show clinical response or lost the allograft. The incidence of acute rejection and borderline changes was 34.4%. The incidences of partial and complete remissions were 16.4% and 27.8%, respectively. Overall 6-years patient and graft survivals were 90.7% and 64.5%, respectively. Among 13 patients of study 2 submitted to the multitarget treatment the median time to diagnosis was 1 month. Mean proteinuria was 8,8g/g and mean serum creatinine was 4,2 mg/dL. The incidence of first biopsy-confirmed FSGSr was 27%. Treatment was started in 4 days. All patients discontinued treatment in a mean time of 27 days, 11 of them (84.6%) due to infectious intercurrences. The study 3 has not detected risk factors for graft loss or remission. Conclusion: This analysis confirms the low, variable and unpredictable rate of FSGSr remission, with treatment options showing variable efficacy and high rate of AE, ultimately leading to inferior graft survival. The main infectious intercurrence was cytomegalovirus (CMV). Multitarget treatment was not a therapeutic option in FSGSr patients of our center.